Predictors of shoulder injuries in collegiate swimmers - Mona Selim Mohamed Faggal; Alaa Eldin Abdelhakeem Balbaa; Mona Hasan Gamal Eldin (Cairo : Mona Selim Mohamed Faggal, 2013)
Shoulder pain and associated glenohumeral (GH) joint movement dysfunctions are common and debilitating conditions. Competitive swimming is a sport long popular all over the world. Shoulder pain is the most common orthopedic problem in competitive swimming. Purpose of this study was to provide descriptive information about characteristics of swimmers and identify significant predictors that were associated with collegiate swimmers shoulder problems
Thesis (Ph.D.) - Cairo University - Faculty of Physical Therapy - Department of Musculoskeletal Disorders
Issued also as CD
Keywords: Scapular posture symmetry; Shoulder injury; Swimmer's shoulder